Diagnosis of pheochromocytoma: a clinical practice guideline appraisal using AGREE II instrument. Issue 4 (18th July 2012) - Yan, Juping; Min, Jie; Zhou, Bo
Abstract: Objective: The objective of this study was to assess the quality of clinical practice guidelines providing diagnostic recommendations on pheochromocytoma (PHEO) using the new Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument and to promote the development of clinical guidelines. Research design and methods: We searched MEDLINE and electronic databases for guidelines published between 2001 and 2010 regarding the diagnosis of PHEO. The methodological quality of guidelines for three fields for the diagnosis of PHEO was evaluated using the new AGREE II instrument by two independent appraisers. We also compared two different types of guidelines to determine the superior guideline. Results: Four special guidelines and six general guidelines related to the diagnosis of PHEO were included in the study. According to AGREE II, two guidelines performed well in recommending biochemical evaluations. One guideline was good for radiodiagnosis, but no guideline was good for recommending genetic testing. The best‐performing domain of the AGREE II instrument was domain 1 (D1) (scope and purpose), while the worst performing domain was D5 (applicability) in both types of guidelines. The special guideline was significantly better than the general guideline in D4 ( P < 0.01), while the general guideline performed better in D6. There were no differences in the other four domains. Conclusions: The quality and rigour of guidelines for the diagnosis of PHEO vary. It is difficult to identify one guideline that performed well in all three fields for the diagnosis of PHEO based on the AGREE II instrument. Therefore, additional studies and greater efforts should be taken to provide high‐quality guidelines that serve as a useful and reliable tool for clinical decision making in diagnosing PHEO according to the AGREE II instrument.